Tristetraprolin Overexpression in Non-hematopoietic Cells Protects Against Acute Lung Injury in Mice - Choudhary, Ishita; Vo, Thao; Bathula, Chandra S.; Lamichhane, Richa; Lewis, Brandon W.; Looper, Jayme; Jeyaseelan, Samithamby; Blackshear, Perry J.; Saini, Yogesh; Patial, Sonika (Frontiers in Immunology, 2020)
Tristetraprolin (TTP) is a mRNA binding protein that binds to adenylate-uridylate-rich elements within the 3’ untranslated regions of certain transcripts, such as tumor necrosis factor (Tnf), and increases their rate of decay. Modulation of TTP expression is implicated in inflammation; however, its role in acute lung inflammation remains unknown. Accordingly, we tested the role of TTP in lipopolysaccharide (LPS)-induced acute lung injury (ALI) in mice. LPS-challenged TTP-knockout (TTPKO) as well as myeloid cell-specific TTP-deficient (TTPmyeKO) mice exhibited significant increase in lung injury albeit these responses were more robust in the TTPKO. Mice with systemic overexpression of TTP (TTPΔARE) were protected from ALI as indicated by significantly reduced neutrophilic infiltration, reduced levels of neutrophil chemoattractants, and histological parameters of ALI. Interestingly, while irradiated WT mice reconstituted with TTPKO hematopoietic progenitor cells (HPCs) showed exaggerated ALI, their reconstitution with the TTPΔARE HPCs mitigated ALI. The reconstitution of irradiated TTPΔARE mice with HPCs from either WT or TTPΔARE donors conferred significant protection against ALI. In contrast, irradiated TTPΔARE mice reconstituted with TTPKO HPCs had exaggerated ALI, but the response was milder as compared to WT recipient that received TTPKO HPCs. Finally, the reconstitution of irradiated TTPKO recipient mice with TTPΔARE HPCs did not confer any protection to the TTPKO mice. These data together suggest that non-HPCs-specific overexpression of TTP within the lungs protects against ALI through downregulation of neutrophil chemoattractants and reduction in neutrophilic infiltration.